Faktor Penyebab Rendahnya Kualitas Pekerjaan Jalan di Kabupaten Sijunjung - Firdaus, Ilyas; Jumas, Dwifitra Y; Anif, Bahrul (Jurnal Talenta Sipil, 2025)
The quality of road work determines the level of safety and comfort of road users. Many road construction works are found to be damaged before their design life, due to the low quality of the road work. Many factors influence the quality of road work. The aim of this research is to identify the factors causing the low quality of road work in Sijunjung Regency, to find the dominant factors, and to find solutions so that the quality of road work meets the established specifications. This research uses a combination approach (mixed methods). A quantitative approach is used to identify the dominant factors causing the low quality of road work in Sijunjung Regency, while a qualitative approach uses research and literature studies such as articles, journals, guidebooks and documents about the quality of road work. From the research results, it was found that the factors that influence the low quality of road work in Sijunjung Regency are Human Resources, Materials, Equipment, Finance, Work Methods and Environment. Meanwhile, the dominant factor that has the most influence is the material factor. Solutions that can be implemented include increasing control and supervision over the management and use of materials, as well as increasing the competence of workers and construction service businesses through outreach, technical guidance, education and training. In addition, it is necessary to provide sanctions or punishment in accordance with applicable regulations to contractors who are negligent in carrying out road work, so that irregularities do not occur again which will cause low quality of road work in the future.